Asuhan Keperawatan Keluaga dengan Implementasi Diet Labu Kuning untuk Penderita Diabetes Melitus di Wilayah Kerja Puskesmas Sukoharjo - Eva Mardiana Hidayah; Rice Hernanda; Sutrisno Sutrisno (Jurnal Ventilator, 2024)
Diabetes mellitus is a chronic metabolic disease characterized by increased blood glucose levels (hyperglycemia) caused by insulin secretion deficiency and / or insulin resistance which over time can cause serious damage to various body systems, especially to nerves and blood vessels, Pumpkin (Cucurbita moschata) is one of the fruits that contains antioxidant compounds Pumpkin (Cucurbita moschata) can also overcome poisoning, clean digestion, and play a role in overcoming hyperglycemia. The purpose of this study was to determine the Nursing Care of Families with the Implementation of the Yellow Pumpkin Diet for Patients with Diabetes Mellitus in the Sukoharjo Health Center Work Area. Data collection methods Data is obtained by interview and observation. The results are written with field notes, then copied in the form of transcripts (structured notes). The activity plan was carried out on Tuesday, June 25, 2024 regarding education on the implementation of the Pumpkin Diet for Diabetes Mellitus Patients in the Sukoharjo Health Center Work Area. The results of the evaluation of the diagnosis of blood sugar instability and given pumpkin diet therapy. The first day before giving pumpkin 250mg/dl after giving pumpkin 247mg/dl on the first day. During the 3 days of giving a diet of yellow pumpkin to 238mg / dl.